Faktor Penentu Pola Kemitraan Antara Petani Lada dan Pedagang Pengumpul di Kawasan Perbatasan Entikong - Nugraha, Aditya; Permatasari, Nia; Komariyati, Komariyati (Perkebunan dan Lahan Tropika, 2026)
This study explores the key factors influencing partnership patterns between pepper farmers and collecting traders in the Entikong border area, West Kalimantan. Agricultural activities in border regions are often constrained by limited access to markets, capital, and infrastructure, making informal partnerships an important support system for farmers. The purpose of this research is to identify the key elements that shape and maintain these partnerships based on farmers’ perceptions. The study used a qualitative approach with primary data collected from 50 pepper farmers selected through purposive and quota sampling. Data were gathered through structured interviews using a Likert-scale questionnaire and analyzed descriptively by calculating mean and standard deviation to assess the level of importance of each variable. The results show that commitment is the most dominant factor in sustaining partnership relationships, followed by trust, which strengthens long-term cooperation. Communication and cooperation were considered moderately important in supporting coordination and information sharing, while conflict management and perceived partnership value were rated lower. Overall, the study highlights that strong commitment, supported by trust and consistent interaction, is essential for maintaining stable partnerships and provides empirical evidence on relational dynamics within agricultural systems in border areas.